1987
DOI: 10.1152/ajpheart.1987.253.2.h317
|View full text |Cite
|
Sign up to set email alerts
|

Coronary input impedance during cardiac cycle as determined by impulse response method

Abstract: The coronary arterial system was characterized by its input impedance determined in systole and diastole from impulse response functions in five dogs. The impulse response technique was verified on a known hydraulic system. A second confirmation was obtained on the circumflex artery: reflected pulses were correlated with site of reflections generated by occlusions. The impulse response indicates discrete reflections, superimposed on the tail of the response, resulting from diffuse reflections. Input impedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…For a wave speed of 20 m/s, this corresponds to a minimal wavelength of 40 cm (wavelength ϭ wave speed/frequency), which is substantially more than twice the typical coronary vessel length. Additional support for the above reasoning is gained from an earlier study by van Huis et al (24) who demonstrated by using impedance analysis that the coronary system consists of a proximal part that can be described by a windkessel and a distal part that is not seen by high-frequency perturbations.…”
Section: Consistency Of Spc With Pressure and Velocity Variations Prementioning
confidence: 91%
“…For a wave speed of 20 m/s, this corresponds to a minimal wavelength of 40 cm (wavelength ϭ wave speed/frequency), which is substantially more than twice the typical coronary vessel length. Additional support for the above reasoning is gained from an earlier study by van Huis et al (24) who demonstrated by using impedance analysis that the coronary system consists of a proximal part that can be described by a windkessel and a distal part that is not seen by high-frequency perturbations.…”
Section: Consistency Of Spc With Pressure and Velocity Variations Prementioning
confidence: 91%
“…17 We then computed coronary arterial resistance and coronary arterial microcirculation resistance on the basis of mean flow, mean arterial pressure, and the coronary impedance spectrum using literature data. 3,26 The capacitance values were adjusted to give physiologically realistic coronary flow and pressure waveforms using literature data. 3 During simulated exercise, the mean flow to the coronary vascular bed was increased to maintain the mean flow at 4.0% of the cardiac output.…”
Section: Choice Of the Parameter Values For The Coronary Modelmentioning
confidence: 99%
“…55 Importantly, this approach can only be applied to the coronary arteries by neglecting the contribution of ventricular contraction. 54 Nonetheless, the threeelement Windkessel method provides a good estimate of the arterial tree beyond model outlets 59 and can be described by three main parameters with physiologic meaning: Rc, C, and Rd. Rc is the characteristic impedance representing the resistance, compliance, and inertance of the proximal artery of interest, C is the arterial capacitance and represents the collective compliance of all arteries beyond a model outlet, and Rd describes the total distal resistance beyond a given outlet.…”
Section: Specification Of Boundary Conditions and Simulation Parametersmentioning
confidence: 99%
“…An LAD blood flow waveform at rest 20 was applied at the model inlet and outlet boundary conditions that replicated flow and pressure in the absence of ventricular contraction were applied using Simvascular. 54 A stent-to-artery deployment ratio of 1:1 was assumed. The stent was modeled as rigid while the modulus of elasticity and thickness of the vessel wall were selected to match the deformation previously observed in response to the imposed resting flow conditions.…”
Section: Artery Implantationmentioning
confidence: 99%